Storytelling and teamwork in the bilingual classroom at university: Impressions and satisfaction from pre-service teachers in the Kamishibai project - Castillo-Rodríguez, Cristina Milagrosa; Cremades-García, Raúl; López-Fernández, Iván (Elsevier, 2022)
The storytelling technique Kamishibai has shown multiple advantages in educational settings. However, there is a lack of studies that deepen on its implementation in teacher training. A total of 114 pre-service teachers (mean age = 20.76 years), enrolled in the Degree of Primary Education at the University of Málaga, participated in a project where they had to design and perform a paper-based theatre for primary-education pupils as a target audience. A semi-structured online survey was administered to determine pre-service teachers’ satisfaction and perceptions towards their Kamishibai and the work in teams. The results revealed that most of the pre-service teachers were satisfied with the team experience. Besides, some benefits were listed: fostering creativity, at university; catching pupils’ attention, fostering creativity and promoting reading, in primary-school context. The Kamishibai implementation goes beyond promoting reading and other linguistic skills in both mother tongue and foreign language; it may be considered a multidisciplinary educative resource to strengthen further cross-curricular competences.
Keywords: Enseñanza bilingüe; Kamishibai; Teamwork; Bilingual education; Pre-service teachers; Storytelling